ANALISIS PENGARUH ASET, JAMINAN, TINGKAT PENDIDIKAN DAN TINGKAT SUKU BUNGA PINJAMAN PERBANKAN TERHADAP KEPUTUSAN PEMBIAYAAN KREDIT - Meidiyustiani, Rinny; Hidayat, Ravindra Safitra; Haryatih, Haryatih (Economic Faculty, Attahiriyah Islamic University, 2019)
This study aims to examine and obtain empirical evidence about the influence of assets, guarantees, level of education and interest rate on SME loans financing decision. Research is descriptive and quantitative data analysis. Statistical analysis using the software program SmartPLS version 2.0. The data used are primary data sample of SMEs that are in Karang Tengah, Ciledug. From the results of the analysis showed that the variables of assets, collateral and interest rates positive influence on the decision of the SMEs credit financing, while the educational level did not affect the decision of the SMEs credit financing. Keywords: assets, guarantees, level of education, interest rates, credit financing decisions